Karakterisasi Farmakognostik dan Skrining Fitokimia Daun Tabebuia rosea sebagai Bahan Baku Obat Herbal - Deka Prismawan; Michael Michael; Felicia Natalia (Pengurus Pusat Ikatan Apoteker Indonesia, 2026)
Tabebuia rosea is a tropical plant with potential as a raw material for traditional medicine. Parts of this plant like leaves, bark, and flower, indicates potential biological activity like antiinflammation, antibacterial, antioxidant, antidiabetic, and antiproliferative. but its pharmacognostic and phytochemical characterization remains limited, especially in the leaves. This study aims to evaluate the pharmacognostic characteristics and phytochemical content of T. rosea leaves as a basis for standardization. Fresh T. rosea leaves were collected, dried, and ground into a fine powder. Evaluations included organoleptic and macroscopic analysis, microscopic examination, moisture content, total ash content, and phytochemical screening for secondary metabolites such as alkaloids, flavonoids, tannins, saponins, coumarins, triterpenoids, and phenolics. The leaves exhibited a lanceolate shape with smooth margins, pointed tips, and pinnate venation. Microscopic analysis revealed diagnostic features such as trichomes, calcium oxalate crystals, and parenchyma. The moisture content was 7.8%, and total ash content was 11.91%. Phytochemical screening confirmed the presence of flavonoids, tannins, phenolics, and alkaloids, while saponins and coumarins were not detected. This study provides fundamental data for the identification and standardization of T. rosea leaf simplisia. The presence of bioactive compounds, particularly flavonoids and alkaloids, supports its potential as a phytopharmaceutical raw material. Further research is needed to isolate and evaluate the pharmacological activities of these compounds.